Application of biocomposites in automotive components: A review - Alam, M.A. (Elsevier, 2020)
Materials play a significant role in daily life and have contributed greatly to the technoeconomic advancement of the modern era. Biocomposites are considered newly developed fourth-generation materials that are considerably high performance and desirable in the light of environmental sustainability and full end-use consumer product degradability. Biocomposites derived via renewable resources offer very interesting potential to benefit manufacturers, the surrounding environment, and consumers as petroleum resources are deteriorating rapidly. This chapter presents an overview of some basic concepts of biocomposite materials and their potential applications in automotive industries. It also addresses the recent advances, current initiatives, and key limitations to be tackled for the implementation of biocomposites at the commercial scale. Moreover, the economic and environmental consequences of biocomposites in the automotive sector are also highlighted in detail. A retrospective review of market trends and forecast analysis of biocomposites has also been addressed and discussed. The study also highlights the potential of natural fibers and biopolymers for commercial applications in the interior and exterior components of cars and a few other applications as well. Â© 2021 Elsevier Ltd All rights reserved.